HALAL FOOD INDUSTRY: REINFORCING THE HALAL PRODUCT ASSURANCE ORGANIZING BODY (BPJPH) IN THE DEVELOPMENT OF THE AMONG URBAN MUSLIM COMMUNITY IN INDONESIA - Bahrudin, Muh.; Iqbal, Muhammad; Saefurrohman, Ghina Ulfa; Walsh, John (AKADEMIKA: Jurnal Pemikiran Islam, 2024)
The halal food industry holds significant promise in the global market, with its importance extending beyond Islamic countries to encompass secular nations and Muslim minorities. Indonesia is a critical player in this industry's development with its substantial Muslim population. The Halal Product Assurance Organizing Body(BPJPH) is pivotal in advancing the halal food sector among urban Muslims in Indonesia. This study examines the role and challenges BPJPH faces in this context and proposes strategies for strengthening its position to enhance the industry's success. This study employs a qualitative approach to investigate the role of BPJPH in fostering the halal industry in Lampung, Indonesia. Data was gathered through in-depth interviews and focus group discussions with halal industry players and relevant stakeholders. Data analysis was conducted thematically while adhering to ethical research principles. The findings underscore the significant role of BPJPH in improving the quality of halal products, enhancing consumer confidence, and providing trusted halal certification. Moreover, through outreach and training, BPJPH increases industry awareness and knowledge about correct halal practices. BPJPH must improve infrastructure, human resources, and stakeholder collaboration to maximize its impact. The study concludes that BPJPH can potentially strengthen Indonesia's halal industrial ecosystem, contributing to economic growth and societal welfare. However, challenges persist, necessitating concerted efforts from BPJPH and stakeholders to innovate and sustain the industry's growth. This research provides valuable insights for developing the halal food industry and underscores the crucial role of BPJPH in ensuring its success.